The impacts of oil export and food production on inflation in African OPEC members - Bala, Umar; Lee, Chin; Kaliappan, Shivee Ranjanee; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study examined the long run impact of oil export and food production on inflation in African OPEC member countries. The countries consist Algeria, Angola, Libya and Nigeria. This study applied Pedroni cointegration test. In addition, dynamic panel ARDL models (PMG and MG estimators) were also used. This study found that the long-run coefficient of oil exports, money supply, exchange rate and GDP are positively related to inflation while food production is negatively related to inflation. The policy makers should maintain a certain level of oil export to minimize the rate of inflation, also to encourage domestic food production to reduce the rate of inflation. Besides that, the study also concludes that increase in money supply and depreciation of exchange rate cause inflation rate. Hence, the policy makers can use the contractionary monetary policy as well as currency control to reduce the inflation rate in OPEC member countries.